The Effectiveness of Using Planting Media Based on Biotechnology Agents on the Growth of Wijayakusuma (Epiphyllum oxypetalum (DC.)Haw.) - Hesti Fitria Dewi; Ida Yayu Nurul Hizqiah; Cartono Cartono; Mimi Halimah (Jurnal Biologi Tropis, 2022)
Wijayakusuma ornamental plant (Epiphyllum oxypetalum (DC.) Haw.) is a plant that is easily propagated by cuttings. To overcome this problem, it is necessary to pay attention to the planting media used. This study aims to determine the effectiveness of providing planting media based on biotechnology agents on the growth of Wijayakusuma ornamental plants. This study is a quasi-experimental quantitative study using a Randomized Block Design, this study used six treatments with four replications. Follow-up test using Duncan's Post-Hoc Test at a level of 5% using SPSS version 26 program. The results of the analysis of various studies stated that planting media based on biotechnological agents with a mixture of burnt husks, cocopeat, raw husks, andam, livestock manure and liquid fertilizer obtained results < 0.05 which means that it has a significant effect on the parameters measured, such as the number of leaves, stem height, and plant root length. These results indicate that the effectiveness of using growing media containing potassium, calcium, phosphorus, through the fermentation process, contains biotechnological agents such as rhizobium, mycorrhizae, and phytohormones that affect plant growth. The most optimal composition of planting media based on biotechnology agents for plants based on Duncan's Post-Hoc test results is T2 treatment with a composition of growing media based on biotechnology agents + roasted husk growing media. Then there is no relationship between climatic factors with the growth of ornamental plants Wijayakusuma. Wijayakusuma plants grow well in places that are not exposed to direct sunlight, normal environmental temperature and humidity, moist soil that is neither too wet nor too dry, and optimal soil pH.